Exploring Non-Visitors’ Attitude Towards Kubah National Park’s Attributes, Roles and Functions - Nor Afiza, Abu Bakar; Dayang Affizzah, Awang Marikan; Salbiah, Edman (UNIMAS Publisher, Universiti Malaysia Sarawak, 2019)
National parks are highly valuable and vital to the ecosystems for countries around the world. In Malaysia, it forms one of the ecotourism products or sites in Malaysia. The swift development and growth of ecotourism particularly in the national parks are inspired by the increased promotion from both tourism operators and the government. Managing national parks require both visitors and non-visitors’ information and their attitudes towards the importance of the park’s attributes, roles and functions. Hence, the purpose of this study is to examine the importance of attributes, roles and functions of national parks in Sarawak, from the perspective of residents and non-residents in Kuching areas (non-visitors). Non-residents include of domestic and foreign tourists, who are found in Kuching at the time of data collection. For these purposes, Kubah National Park (KNP), one of the most visited national parks in Sarawak, has been selected as a case study. Non-visitors’ were surveyed as they might be potential visitors in the future. Even if they will not visit the area in the future, the existence of the park would also benefit them indirectly as well as their future generations. Such indirect benefits or values are normally referred as non-use values. The non-use values refer to the values that human derived from the goods and services independent of any present or future use that people might make of those goods (Beukering et al., 2007). It usually divided between the bequest values and existence values. Face-to-face interviews involving selected respondents in Kuching areas were conducted in September to December 2018. A structured questionnaire was developed as the primary research instrument. Only respondents over 18 years of age who were willing to participate, were being interviewed. Results indicate that non-visitors have positive attitudes towards the attributes, roles and functions of KNP. The majority of participating respondents placed higher priority on the protection of the natural environment and wildlife as well as preservation of the biological diversity of the environment. The examination of how visitors and public perceive the roles and roles and functions of KNP would assist in delivering appropriate management and sustainable conservation of the area. This information is essential in understanding of the public or non-visitors’ attitude and perception of KNP’s attributes, roles and functions.